A time-domain finite element method for dynamic viscoelastic solution of layered-half-space responses under loading pulses. (November 2015) - Xu, Qinwu; Prozzi, Jorge A.
Highlights: We developed a dynamic viscoelastic response model and finite element solution for layered half-space. The combined Houbolt, central and forward finite difference method is proposed for time discretization. It is able to model the temperature and space-dependent material properties. We validated the approach for a multilayer pavement structure on soil. The dynamic viscoelastic model considering damping could more accurately emulate structural responses. Abstract: This research develops a dynamic viscoelastic model, a Galerkin based time-domain finite element method, and computer program for simulating layered half-space responses under loading pulses. A combined Houbolt, central finite-difference (FD) and forward FD method is proposed for time discretization of acceleration and velocity to reduce time-step lengths. Compared to existing methods, the developed approach has advantages that it: (1) captures the coupled effects of material viscoelasticity, dynamics and system damping, which fosters understanding structural responses and material deformations; (2) is able to model temperature and space-dependent material properties. The model is implemented and validated for a multilayer pavement-soil structure.